1997
DOI: 10.3354/meps155199
|View full text |Cite
|
Sign up to set email alerts
|

Food resource utilization by juvenile Baltic cod Gadus morhua:a mechanism potentially influencing recruitment success at the demersal juvenile stage?

Abstract: Pelagic and demersal juvenile Baltic cod Gadus morhua L. were collected during surveys in the Bornholm Basin (Baltic Sea) in autumn 1994. Stomach contents were examined for prey composition in order to evaluate the potential importance of the pelagic and demersal habitats for recruitment success. Juvenile cod less than 40 mm fed exclusively on pelagic prey such as copepods and cladocerans. Between 40 and 50 mm the juveniles began to consume benthic prey such as mysids and amphipods; however, copepods were stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 24 publications
2
47
0
1
Order By: Relevance
“…The diversity of potential prey species in the Baltic Sea is limited, forcing newly settled cod to feed on the same size-range and species of prey as fish of a larger size (Hüssy et al 1997). The major prey items during the first months of the demersal stage are benthic and semi-benthic invertebrates such as mysids and amphipods (Hüssy et al 1997), whose highest densities are found below 25 m (Aschan 1988, Rudstam & Hansson 1990).…”
Section: Prey Availabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The diversity of potential prey species in the Baltic Sea is limited, forcing newly settled cod to feed on the same size-range and species of prey as fish of a larger size (Hüssy et al 1997). The major prey items during the first months of the demersal stage are benthic and semi-benthic invertebrates such as mysids and amphipods (Hüssy et al 1997), whose highest densities are found below 25 m (Aschan 1988, Rudstam & Hansson 1990).…”
Section: Prey Availabilitymentioning
confidence: 99%
“…The major prey items during the first months of the demersal stage are benthic and semi-benthic invertebrates such as mysids and amphipods (Hüssy et al 1997), whose highest densities are found below 25 m (Aschan 1988, Rudstam & Hansson 1990). On the slope, feeding conditions may therefore have been more favourable than on the shallow bank due to greater variety and quantity of prey items, as suggested by Hüssy et al (1997).…”
Section: Prey Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Herring in particular are important consumers of a key prey item of the diets of larval and pelagic 0-group cod, Pseudocalanus spp. (Hussy et al 1997;Voss et al 2003;Möllmann et al 2004;. This copepod species is presently relatively rare in the Baltic sea due to both a multi-annual change in hydrographic conditions (i. e., lower salinity; and predation by herring [Casini, 2008 3715 /id;Möllmann, 2008 3716 /id;Casini et al 2009].…”
Section: Other Fish Stocksmentioning
confidence: 99%
“…Cod spend their first months of life in pelagic environments feeding on zooplankton. When reaching a sufficient size (approximately 5 cm), cod become benthivorous and commonly forage on various benthic crustaceans associated with vegetated habitats (Hüssy et al 1997). As cod grow in size, the proportion of fish such as herring and sprat in their diet increases.…”
Section: Introductionmentioning
confidence: 99%